2020
DOI: 10.3390/molecules25184310
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Combined Admistration of Imatinib and Sorafenib in a Murine Model of Liver Fibrosis

Abstract: Liver fibrosis is defined as excessive extracellular matrix deposition in the hepatic parenchyma as a consequence of complex interactions among matrix-producing hepatic stellate cells (HSCs) and liver-resident and infiltrating cells. In addition to the liver, the process of fibrosis may represent end-stage disease of several diseases including kidneys, lungs, spleens, heart, muscles and at certain extent, the central nervous system and the peripheral nerves. To date, antifibrotic treatment of fibrosis represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Additionally, animals treated with sorafenib showed HSC phenotype amelioration, resulting in PP reduction [188]. In accordance with this, it has been demonstrated that sorafenib ameliorates the HSC phenotype by decreasing ECM deposition and the expression of fibrinogenic molecules in liver fibrosis [189].…”
Section: Targeting Other Vascular Alterationssupporting
confidence: 63%
See 1 more Smart Citation
“…Additionally, animals treated with sorafenib showed HSC phenotype amelioration, resulting in PP reduction [188]. In accordance with this, it has been demonstrated that sorafenib ameliorates the HSC phenotype by decreasing ECM deposition and the expression of fibrinogenic molecules in liver fibrosis [189].…”
Section: Targeting Other Vascular Alterationssupporting
confidence: 63%
“…Tyrosine kinase receptor inhibitors were suggested as a therapeutic option for angiogenesis occurring in advanced CLD [188,189]. In this context, rats with intrahepatic PH treated with sorafenib showed the inhibition of endothelial angiogenic and proliferative markers such as VEGFR-2 and PDGFRβ through the suppression of the Raf/MEK/ERK signalling pathway.…”
Section: Targeting Other Vascular Alterationsmentioning
confidence: 99%
“…Sunitinib is an indolin-2-one structural analog that is taken orally and inhibits various RTKs including VEGFR1/2/3, PDGFR, FGFR, and c-Kit [ 128 ]. Sunitinib demonstrated potent anti-tumor and anti-angiogenesis effects in a variety of cancer types in clinical trials.…”
Section: Introductionmentioning
confidence: 99%